Effect of concrete infill walls on the progressive collapse performance of precast concrete framed substructures. (November 2020) - Wang, Feiliang; Yang, Jian; Nyunn, Sandy; Azim, Iftikhar
Abstract: Precast concrete (PC) frames are considered vulnerable to progressive collapse as inadequate ties between precast components can lead to a loss of structural continuity. In previous studies, slabs and masonry infill walls were found able to mitigate the progressive collapse behaviours of reinforced concrete (RC) frames. However, progressive collapse physical tests of PC frames with prefabricated concrete infill walls are scarce. Therefore, laboratory tests of three PC specimens, including bare frame, semi-infilled frame and fully infilled frame, are conducted in the paper under a centre column loss scenario. Reinforcement detailing and specimen setup are introduced and recorded results are discussed. Observations during test indicate that failure of the PC bare frame is governed by the pull out of anchorage bars at the beam-exterior column joint. Moreover, the infilled specimen leads to a substantial increase in load-carrying capacity at both the flexural stage and catenary action stage when compared with the bare frame. Based on numerical simulation, it can be concluded that the size and position of the opening have a significant impact on structural resistance of an infilled PC frame, especially on the resistance at the flexural stage. Highlights: Experimentalstudy on progressive collapse performance of PC beam-column sub-frame with and without infill walls. Numerical simulation of the test specimen established using micro-model strategy. Good agreement between the model predictions and experimental outcomes. The effects of infill wall configuration on the structural behaviour were revealed based on parametric studies.